The Association Between Distressed Community Index and Clinical Outcomes Following Total Ankle Arthroplasty - C. James Kim BA; Justin Tsai MD; David I. Pedowitz MD, MS; Daniel Fuchs MD; Joseph T. O’Neil MD; Rachel Shakked MD; Brian S. Winters MD; Joe Daniel DO (Foot & Ankle Orthopaedics, 2023)
Category: Ankle Arthritis; Ankle Introduction/Purpose: Socioeconomic deprivation factors such as income levels, race and ethnicity, low education level, and insurance status have been shown to be associated with suboptimal postoperative outcomes for patients undergoing orthopedic surgeries, including certain foot and ankle procedures1–3. Total ankle arthroplasty (TAA) is a surgical treatment for end-stage ankle joint disease that has seen a significantly increased utilization over the past two decades4. Distressed community index (DCI) is a score that represents a community’s level of well-being across the United States5, with higher scores representing greater distress experienced in the community. The purpose of this study was to determine if there is any association between DCI scores and complications rates along with functional outcomes following primary TAA. Methods: 566 patients who underwent primary TAA between 2015 and 2019 at our institution were identified. Patients’ residence zip codes at the time of surgery were obtained and the corresponding DCI scores (0-100) were determined using DCI data provided by the Economic Innovation Group for the same time period (2015-2019). Scores were divided into quintiles. Patient age, sex, body mass index, race, ethnicity, rheumatic disease status, Osteoporosis status, Charlson comorbidity index, alcohol use, smoking status, length of hospital stay, discharge to rehabilitation facility, depression history, anxiety history, and marital status were obtained. Postoperative FAAM-VAS scores at 6 months, 1-year, and 2-years were compared to their preoperative scores. Revision, infection, steroid injection, loose body or hardware removal, irrigation and debridement, periprosthetic fracture, and tibial/talar exostectomy were noted. Analysis of variance (ANOVA) was used to determine the statistical significance of differences in the rate of subsequent complications and interventions related to index TAA. Results: 88/566 (15.5%) of all patients required at least one operative intervention related to the index TAA. Patients in the 4th DCI quintile experienced the highest rate of subsequent procedures at 18.3% while those in the 5th DCI quintile experienced the lowest rate at 10.6%. The differences in rate of subsequent operative intervention across DCI quintiles was not statistically significant (p=0.775). However, the rates of revision and infection were the highest for patients in the 4th and 5th DCI quintiles, respectively. The differences in improvement of FAAM Overall and VAS Pain scores at 6 months, 1-year, and 2-years from index surgery were not statistically significant. Those in the 5th quintile experienced the least improvement in FAAM Overall at the 1- year and 2-year postoperative time points. Conclusion: DCI score was not associated with increased rates of postoperative complication requiring operative intervention and FAAM-VAS scores in patients undergoing primary TAA. However, patients in the 5th quintile of DCI experienced non-significantly lesser improvement in FAAM-VAS scores up to 2-years from surgery.